2004
DOI: 10.1021/ja047438+
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of Potent, Conformationally Constrained Smac Mimetics

Abstract: Intermolecular electron transfer (ET) between the free phenothiazine donor (PH) and its cation radical (PH*+) proceeds via the [1:1] precursor complex (PH)(2)*+ which is transiently observed for the first time by its diagnostic (charge-resonance) absorption band in the near-IR region. Similar intervalence (optical) transitions are also observed in mixed-valence cation radicals with the generic representation: P(br)P*+, in which two phenothiazine redox centers are interlinked by p-phenylene, o-xylylene, and o-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
146
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 15 publications
3
146
0
Order By: Relevance
“…A number of studies have demonstrated that SMAC and SMAC mimetics potentiate apoptosis induced by anticancer agents, including chemotherapeutic drugs and irradiation, in human cancer cells (Fulda et al, 2002;Arnt and Kaufmann, 2003;Giagkousiklidis et al, 2005;Zhao et al, 2006). Efforts have also been made to develop improved SMAC mimetic agents (Li et al, 2004;Sun et al, 2004). However, the precise function of SMAC in promoting apoptosis induced by anticancer agents was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that SMAC and SMAC mimetics potentiate apoptosis induced by anticancer agents, including chemotherapeutic drugs and irradiation, in human cancer cells (Fulda et al, 2002;Arnt and Kaufmann, 2003;Giagkousiklidis et al, 2005;Zhao et al, 2006). Efforts have also been made to develop improved SMAC mimetic agents (Li et al, 2004;Sun et al, 2004). However, the precise function of SMAC in promoting apoptosis induced by anticancer agents was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Using this approach, we have designed compound 1 (SM-122) as a conformationally constrained, Smac AVPI mimetic containing a [8,5] bicyclic system ( Figure 2) and evaluated its binding affinities to XIAP BIR2 and BIR3 proteins. To facilitate the investigation of the molecular mechanism of action for Smac mimetics, we have also designed a biotinylated analogue of SM-122 (2, named BL-SM-122, Figure 2).…”
Section: Design Of a Cell-permeable Monovalent Smac Mimeticmentioning
confidence: 99%
“…Tripeptide BIR 3 inhibitors with unnatural amino acids have also been identified by Sun et al 61,62 who modified a series of SMAC-pseudomimics and tested their binding to the BIR 3 domain of XIAP by NMR. Binding of peptides to BIR 3 was confirmed by a fluorescent polarization assay.…”
Section: Bir 3 Inhibitorsmentioning
confidence: 99%